REAKTUALISASI NILAI SILA KEDUA PANCASILA DALAM MENGHADAPI INDIVIDUALISME DI KALANGAN MAHASISWA: SUATU SYSTEMATIC LITERATURE REVIEW - Azzahra Khayla Safira Adya Putri; Laily Zakiyaturrahmah; Dian Triwulansari; Ditho Triwahyu Syahrullah; Ivan Widya Kanaka; Kusnul Khotimah (JURNAL ILMIAH NUSANTARA, 2026)
The development of the digital era and globalization has brought significant changes to students’ behavioral patterns, one of which is the emergence of individualistic attitudes among university students. Individualism is an attitude that can reduce empathy, social concern, and the spirit of mutual cooperation within the campus environment. This study aims to examine how the reactualization of the values contained in the second principle of Pancasila, Just and Civilized Humanity, can serve as a solution to overcome individualism among students. The results of this study show that the humanitarian values in Pancasila promote mutual respect, empathy, and concern for others. The implementation of these values can be carried out through social activities, academic collaboration, and strengthening character education within the campus environment. Therefore, the reactualization of Pancasila values plays an important role in building solidarity and social awareness among students.